A kinetic approach to predict the potential effect of malaxation time-temperature conditions on extra virgin olive oil extraction yield. (February 2017) - Trapani, S.; Guerrini, L.; Masella, P.; Parenti, A.; Canuti, V.; Picchi, M.; Caruso, G.; Gucci, R.; Zanoni, B.
Abstract: An original kinetic study of both oil coalescence phenomena and potential extra virgin olive oil extraction yield (i.e. apparent Extractability Index) was carried out at different malaxation time-temperature conditions using Abencor lab equipment to process olives (Frantoio cv) of a known degree of ripeness. The apparent Extractability Index was modelled at every malaxation temperature by pseudo first-order kinetics, where the yield rate constant was temperature dependent following the Arrhenius equation ( k 0  = 7.50 10 7  min −1 ; Ea  = 54512 J/mol). Oil droplet coalescence, which was expressed as a relative variation in the percentage of oil droplets with a diameter of >30 μm, proved to be an time-dependent phenomenon only; the pseudo zero-order kinetics modelling was statistically significant, where the coalescence rate constant was equal to 0.033 min −1 . The above kinetics were applied in order to propose a synoptic chart to predict the potential effect of malaxation in isothermal conditions on EVOO extraction yield. Highlights: An original experimental approach was used to study olive paste malaxation. A time-temperature kinetic study was applied to predict malaxation phenomena. An apparent Extractability Index and oil droplet coalescence phenomena were considered. A synoptic chart was proposed to predict the potential effect of malaxation on yield. Phenomena that condition oil extraction yield changed as a function of temperature.